The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1748-0159.2009.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of restaurant inspection disclosure systems as a means of communicating food safety information

Abstract: The World Health Organization estimates that up to 30% of individuals in developed countries become ill from food or water each year. Up to 70% of these illnesses are estimated to be linked to food prepared at foodservice establishments. Consumer confidence in the safety of food prepared in restaurants is fragile, varying significantly from year to year, with many consumers attributing foodborne illness to foodservice. One of the key drivers of restaurant choice is consumer perception of the hygiene of a resta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…If this is true, it also draws into question the benefits of posting health inspections data if it cannot be guaranteed that all facilities are being inspected without bias or subjectivity. It has been reported that consumers desire both health inspection and hygiene information for food service facilities, and it has an effect on their food service choices (6,10). Assuming this is the case, then the data presented here support the position that there is a need for greater standardization and guarantee of objective results when making inspection information available to consumers (10).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…If this is true, it also draws into question the benefits of posting health inspections data if it cannot be guaranteed that all facilities are being inspected without bias or subjectivity. It has been reported that consumers desire both health inspection and hygiene information for food service facilities, and it has an effect on their food service choices (6,10). Assuming this is the case, then the data presented here support the position that there is a need for greater standardization and guarantee of objective results when making inspection information available to consumers (10).…”
Section: Discussionsupporting
confidence: 84%
“…We believe these results provide quantitative data to support previous qualitative research, indicating that biases do occur during inspections (18). To this end, our data raise interesting questions regarding the value of releasing food inspection results to the public, who could use it as a guide to assure that they are choosing ''safe'' establishments, another issue that has recently been raised in the literature (10).…”
Section: Discussionmentioning
confidence: 97%
“…The openness and transparency provides a framework to increase optimistic trust and potentially reduce mistrust (de Jonge et al, 2008). Restaurants with strong food safety cultures are already able to do this through the restaurant inspection disclosure systems established in a number of locations around the world (Filion & Powell, 2009). A turkey processing plant in South Dakota constantly monitors its operations with by video cameras that can be accessed by auditors or USDA inspectors at any time (Keen, 2006).…”
Section: Marketing Food Safetymentioning
confidence: 99%
“…While important it is extremely difficult to link it to the prevalence and use of posted inspection grades. Indeed, the correlation between inspection scores and foodborne disease outbreaks is inconsistent (Filion and Powell 2009) and empirically hard to identify. It relies entirely on restaurant patrons correctly identifying the foodborne illness and attributing its source, which is difficult to do for a number of reasons (duration of latency, expectations about food safety, proclivities towards gastrointestinal symptoms) (Jones and Angulo 2006;Mead et.…”
Section: B Empirical Literature Reviewmentioning
confidence: 99%
“…Municipalities across the U.S. grade the performance of public schools, street cleanliness is frequently scored and graded, and the Straphangers Campaign in New York City even produces a "report card" ranking the performance of each subway train line. One of the more recent grading initiatives applies to restaurants' food safety compliance, a policy that has taken hold in cities across the globe (Filion and Powell 2009).…”
Section: Introductionmentioning
confidence: 99%